Radiofrequency denervation for chronic back pain: a systematic review and meta-analysis - Chappell, Mary Elizabeth (BMJ Open, 2020)
OBJECTIVES: To assess the effectiveness of radiofrequency denervation (RD) of lumbosacral anatomical targets for the management of chronic back pain. DESIGN: Systematic review and meta-analysis of randomised controlled trials (RCTs). METHODS: A database search (Medline, Medline in Process, Embase, CINHAL and the Cochrane library) was conducted from January 2014 to April 2019 for placebo or no-treatment controlled trials of RD for the management of chronic back pain. Included trials were quality assessed using the Cochrane Risk-of-Bias Tool and the quality of outcomes assessed using the Grading of Recommendations, Assessment, Development and Evaluations (GRADE) approach. Meta-analysis was conducted to calculate mean difference (MD) in post-treatment Pain Score. RESULTS: Nineteen RCTs were included in the review. There appears to be short-term pain relief (1–3 months) provided by RD of the sacroiliac joint (five trials, MD −1.53, CI −2.62 to 0.45) and intervertebral discs (four trials, MD −0.98, CI −1.84 to 0.12), but the placebo effect is large and additional intervention effect size is small (<1 on an 11 point (0–10) Pain Scale). Longer-term effectiveness (>6 months) is uncertain. CONCLUSIONS: RD of selected lumbosacral targets appears to have a small, short-term, positive effect for the management of patients with chronic back pain. However, the quality of evidence for the majority of outcomes is low or very low quality and there is still a degree of uncertainty, particularly around the duration of effect.